PERSEPSI MASYARAKAT PESISIR TERHADAP KERUSAKAN MANGROVE DI DESA POKA KOTA AMBON - Eygner Gerald Talakua; Yoisye Lopulalan (Universitas Pattimura, 2023)
In mid-2022, there was damage to mangroves in Poka Village, precisely in front of the PT State Electricity Company (PT PLN) Diesel Power Plant (PLTD-Poka), allegedly due to accidental exposure to waste due to pipe leaks during bridge construction activities. If you look closely, the mangrove damage that occurs on the coast in front of the PLTD-Poka is not only caused by waste but also by community rubbish. Making coastal communities in Poka Village the driving force for mangrove conservation raises the question, namely, what is the current attitude of coastal communities in Poka Village towards mangrove damage? One component of attitude that is interesting to study is perception. Based on this, it is important to conduct research on coastal communities' perceptions of mangrove damage in Poka Village, Ambon. This research method is a case study, a sample of 61 people are heads of families in coastal communities around the mangrove damaged area in Poka Village which was determined using the Isaac and Michael equation and taken using simple random sampling. Data obtained through primary and secondary data collection were analyzed using a Likert scale approach. The five scale scores were analyzed by modifying the value equation, mean, interval and indicator index criteria for the question instrument. The results of the research show that the perception of coastal communities in Poka Village regarding mangrove damage is knowing or positive. This perception is formed from: sight (knowing about the existence of mangroves), feeling (feeling the benefits of mangroves indirectly), and utilization (using mangrove resources directly).